Development and validation of a patient-reported measure of compassion in healthcare: the Sinclair Compassion Questionnaire (SCQ). Issue 6 (16th June 2021) - Sinclair, Shane; Hack, Thomas F; MacInnis, Cara C; Jaggi, Priya; Boss, Harrison; McClement, Susan; Sinnarajah, Aynharan; Thompson, Genevieve
Abstract : Objectives: Compassion is a key indicator of quality care that is reportedly eroding from patients' care experience. While the need to assess compassion is recognised, valid and reliable measures are lacking. This study developed and validated a clinically informed, psychometrically rigorous, patient-reported compassion measure. Design: Data were collected from participants living with life-limiting illnesses over two study phases across four care settings (acute care, hospice, long term care (LTC) and homecare). In phase 1, data were analysed through exploratory factor analysis (EFA), with the final items analysed via confirmatory factor analysis (CFA) in phase 2. The Schwartz Center Compassionate Care Scale (SCCCS), the revised Edmonton Symptom Assessment Scale (ESAS-r) and Picker Patient Experience Questionnaire (PPEQ) were also administered in phase 2 to assess convergent and divergent validity. Setting and participants: 633 participants were recruited over two study phases. In the EFA phase, a 54-item version of the measure was administered to 303 participants, with 330 participants being administered the final 15-item measure in the CFA phase. Results: Both EFA and CFA confirmed compassion as a single factor construct with factor loadings for the 15-item measure ranging from 0.76 to 0.86, with excellent test–retest reliability (intraclass correlation coefficient range: 0.74–0.89) and excellent internal reliability (Cronbach's alpha of 0.96). The measure was positively correlated with the SCCCS (r=0.75, p<0.001) and PPEQ (r=0.60, p<0.001). Participants reporting higher experiences of compassion had significantly greater well-being and lower depression on the ESAS-r. Patients in acute care and hospice reported significantly greater experiences of compassion than LTC residents. Conclusions: There is strong initial psychometric evidence for the Sinclair Compassion Questionnaire (SCQ) as a valid and reliable patient-reported compassion measure. The SCQ provides healthcare providers, settings and administrators the means to routinely measure patients experiences of compassion, while providing researchers a robust measure to conduct high-quality research.